The acute effects of a preload upper-body power exercise on 50-m freestyle performance in youth swimmers - Hill, V.; Patterson, S.; Buckthorpe, M.; Legg, H. S. (The Journal of Strength and Conditioning Research, 2024)
This study aimed to investigate the acute effects of a medicine ball slam and the optimal recovery time required to induce a postactivation performance enhancement (PAPE) response on 50-meter freestyle swimming performance. Twenty-four (13 female, 11 male) competitive, adolescent swimmers (mean ± SD: age, 16.7 ± 1.2 years; height, 173.3 ± 6.7 cm; mass, 63.1 ± 6.4 kg) participated in a randomized crossover study. After the PAPE intervention (3 × 5 medicine ball slams), subjects had 1-minute, 4-minute, and 8-minute recovery periods before a 50-m maximal freestyle swim. A 1-way repeated-measures ANOVA revealed that different recovery times elicited changes in 50-m performance (F = 12.12, p < 0.0005). After 4 minutes of recovery, 50-m performance was 1.6% (0.47 seconds) faster (95% confidence interval [CI] [0.17-0.77], p < 0.001). When the data were split by sex, after 4 minutes of recovery, 50-m performance was 2% (0.64 seconds) faster for women (95% CI [0.279-0.998], p < 0.001). In conclusion, an upper-body power exercise, before performance, can induce a PAPE response and enhance 50-m freestyle performance after a 4-minute recovery period.